Central American Program for Integrated Coffee Rust Management (PROGAGICA). Climante change mitigation and adaptation measures and natural disaster risk reduction - Centro de Gestión del Conocimiento y Cooperación Horizontal (CGCCH) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
6 pages